Naloxone inhibits nicotine-induced receptor current and catecholamine secretion in bovine chromaffin cells - Tomé, Ângelo R. (2001)
Nicotine-induced catecholamine (CA) secretion and inward ionic currents were inhibited by the opioid antagonist naloxone in cultured bovine chromaffin cells. Naloxone inhibited nicotine-induced CA secretion, as detected by an on-line real-time electrochemical technique, in a dose-dependent manner (IC50=29 [mu]M). In voltage-clamped chromaffin cells, nicotine (10 [mu]M) evoked an average peak inward current of -146 pA that was inhibited by low concentrations of naloxone (42% at 0.1 [mu]M). The antagonist also inhibited total charge influx associated with nicotinic receptor activation (53% at 0.1 [mu]M). This provides strong evidence that naloxone modulation of nicotine-induced CA secretion does not involve opioid receptors but results from the direct interaction with the nicotinic receptor itself, which might also be the case for other related opioid compounds.